2003
DOI: 10.1007/s00438-003-0811-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of telomere-subtelomere junctions in Silene latifolia

Abstract: Telomere-associated regions represent boundaries between the relatively homogeneous telomeres and the subtelomeres, which show much greater heterogeneity in chromatin structure and DNA composition. Although a major fraction of subtelomeres is usually formed by a limited number of highly repeated DNA sequence families, their mutual arrangement, attachment to telomeres and the presence of interspersed unique or low-copy-number sequences make these terminal domains chromosome specific. In this study, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The X43.1 repeat makes up 1.0–1.1% of the genome (9.3–10.0×10 4 copies/1C); its reconstructed consensus of 313 bp includes two regions that were duplicated in some monomers (Fig. 4), fully corresponding to the previously reported genomic sequences [8], [27], [28]. As this repeat has been subject to extensive characterization including FISH localization of its sequence variants [29], we did not investigate it further and used the probe derived from its consensus only in combination with other probes as a marker for discriminating X and Y chromosomes (it labels both arms of X but only one on the Y chromosome, Fig.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The X43.1 repeat makes up 1.0–1.1% of the genome (9.3–10.0×10 4 copies/1C); its reconstructed consensus of 313 bp includes two regions that were duplicated in some monomers (Fig. 4), fully corresponding to the previously reported genomic sequences [8], [27], [28]. As this repeat has been subject to extensive characterization including FISH localization of its sequence variants [29], we did not investigate it further and used the probe derived from its consensus only in combination with other probes as a marker for discriminating X and Y chromosomes (it labels both arms of X but only one on the Y chromosome, Fig.…”
Section: Resultssupporting
confidence: 62%
“…The cluster CL87 corresponded to the satellite 15Ssp [27], [28], with about 1.5×10 4 copies of the 159 bp monomer occurring in the genome (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…The subtelomeric locations of these repeats were confirmed mostly by in situ hybridization on somatic metaphase chromosomes. In some studies, the close physical association of these repeats with telomeres was demonstrated by either fiber-FISH (Cheng et al 2001; Zhong et al 1998; Dechyeva and Schmidt 2006; Sykorova et al 2003) or by repeat junction cloning and sequencing (Fajkus et al 1995; Sykorova et al 2003). We demonstrated that both CL14 and CL34 repeats locate very close to the telomeric ends of potato chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…(62) In large genomes, the prominent heterochromatic subtelomeres are enriched for the multicopy repetitive sequences occurring at many chromosome ends and therefore possess an extensive homology that might promote homologous recombination. These regions also contain DNA sequences with some characteristics of primary structure, such as short direct and inverted repeats and AT-rich regions (63,64) that are thought to boost illegitimate recombination (IR). For example, we analyzed the structure of DNA sequence (spacer) inserted between tandem monomers of highly repetitive families pSc200 and pSc250 localized in most subtelomeres of rye chromosomes.…”
Section: Subtelomeresmentioning
confidence: 99%
“…A similar heterogeneity in chromatin structure has been found at telomere-subtelomere junctions of another plant, Silene latifolia. (63) It is difficult to explain the biological meaning, if any, of the telomere-specific features in nucleosome size and kinetics of the nucleosome degradation.…”
Section: Rap1 Hrap1mentioning
confidence: 99%